A critical review of studies related to construction and computation of Sustainable Development Indices. (May 2020) - Kwatra, Swati; Kumar, Archna; Sharma, Prateek
Highlights: Provides evolution of indices measure development and sustainable development. Describe key characteristics of a good Index. Discusses frameworks used in developing Sustainable Development Indices (SDIs) Discusses the steps in construction of Composite SDI based on aggregated framework. Approaches and levels of application of the SDIs used across globe. Abstract: Sustainable development is a multi-dimensional concept, which emphasizes integration and striking a dynamic balance between economic, social and environmental aspects in a region, to ensure inter-generational and intra-generational equity. One of the major tools to address sustainability concerns is to have indices, which can measure the performance of a region on various dimensions of sustainable development. The review suggests there are various indices that are available at the global scale that compare different countries on different aspects of sustainability; however, a limited number of studies have been reported at regional scale. Further, the paper appraises about the various approaches and frameworks used to develop these Sustainable Development Indices (SDIs). The merits and demerits of these approaches and frameworks have been discussed. The review finds that top-down approaches have been generally employed for construction of SDIs. However, bottom-up approaches which are rarely used, also need to be developed in order to construct robust, contextual and consensus based SDIs. The review shows that composite SDIs are the most common form of framework used across the globe. Most studies have been found to use 30–60 indicators for development of SDIs. The key steps to be followed for construction of Composite Sustainable Development Indices (CSDIs) have been reviewed in detail. The review finds variable processes and steps followed by different studies for development of SDIs. Based on the review, research gaps have been identified and recommendations on steps to be followed in construction of new CSDI have been provided. The review also reveals that most studies have focused on assessment of current state of sustainable development, a limited number where the trends have been studies; no study related to the future projections/predictions of the SDI has been reported in the literature.